The Impact of Architecture design quality in build competitiveness for contracting companies in The Ministry of Housing and Construction of Iraq - الخفاجي, نعمة عباس; العامري, عامر عبداللطيف; الكعبي, مصدق حنون (Journal of Economics and Administrative Sciences, 2017)
The study aimed at interpreting the role of architectural design quality in in build competitiveness model in accordance with the proposal included the idea of ​​architectural design quality for its removal; interesting design factors of the environment, good design of the spaces, and design aesthetic explanatory variable. The competitiveness dimensions; the level of innovation, stimulate research, and the quality of the company's products, and activating the role of human resources, entrepreneurship, profitability, market share and competitiveness, variable responsive. The study of construction companies in the Ministry of Housing and Construction has taken the Iraqi society for the study. The sample consisted of (48) managers from senior management there. The questionnaire adopted data collection tool that was processed program (SPSS v.20) to extract the results of Cronbach's alpha, and the arithmetic mean, standard deviation, correlation, and analysis of multiple linear regression, the study has resulted in the following conclusions:1- High level of care managers architectural design quality and its dimensions, and building Competitiveness and its dimensions in the construction companies which shows the depth of knowledge and awareness of their technological aspects, economic, and environmental and sustainable for of its business and operations.2- The existence of a significant impact in part to the quality of architectural design in dimensions interesting design factors of the environment and aesthetic design to build a competitiveness and dimensions are collectively and individually.3- The possibility of using the architectural design quality in the interpretation of the estimated change the dimensions of competitiveness partially. 4- Proven the validity of the idea of ​​a model study in the interpretation of the potential ability of contractors to build competitiveness Changes in terms of awareness of its directors architectural design quality.